Poem to be sung - Ndyoko, Nomtha (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2018)
My collection of poems expresses the complexities that exist beneath the surface of my life "“ my tongue, our bleak country, the politics of having a dark skin, my ancestors who speak to me in unexplainable ways, and the speech of nature "“ the wind, the sea, death, birds. It is in writing poems and songs that I make a space to be alive, a space to meet my ancestors and to say the unsayable. The poems move between the ordinary, the magical, the abject, and the spiritual, often expressing the contradictions that exist within life. The main influence on my poetry has come from music, from African jazz musicians such as Zim Ngqawana, Thandiswa Mazwai and Msaki Mvana. Literary influences have come from Spanish poets such as Juan Ramón Jiménez, whose strong imagery and short lines capture profound emotion, and from ancient Chinese poetry that moves in a fluid and minimal way. I have also been inspired by the African spirituality expressed in Mazisi Kunene's poetry and the down-to-earth associative poetry of Mangaliso Buzani and Mxolisi Nyezwa.
Keywords: Creative writing (Higher education) -- South Africa; South African poetry (English) -- 21st century